Development and validation of a novel patient‐reported treatment satisfaction measure for hyperfunctional facial lines: facial line satisfaction questionnaire. (12th August 2015) - Pompilus, Farrah; Burgess, Somali; Hudgens, Stacie; Banderas, Benjamin; Daniels, Selena
Summary: Background: Facial lines or wrinkles are among the most visible signs of aging, and minimally invasive cosmetic procedures are becoming increasingly popular. Aims: The aim of this study was to develop and validate the Facial Line Satisfaction Questionnaire (FLSQ) for use in adults with upper facial lines (UFL). Methods: A literature review, concept elicitation interviews ( n = 33), and cognitive debriefing interviews ( n = 23) of adults with UFL were conducted to develop the FLSQ. The FLSQ comprises Baseline and Follow‐up versions and was field‐tested with 150 subjects in a US observational study designed to assess its psychometric performance. Analyses included acceptability (item and scale distribution [i.e. missingness, floor, and ceiling effects]), reliability, and validity (including concurrent validity). Results: In total, 69 concepts were elicited during patient interviews. Following cognitive debriefing interviews, the FLSQ‐Baseline version included 11 items and the Follow‐up version included 13 items. Response rates for the FLSQ were 100% and 73% at baseline and follow‐up, respectively; no items had excessive missing data. Questionnaire scale scores were normally distributed. Most domain scores demonstrated good internal consistency reliability (Cronbach's α ≥ 0.70). Most items within their respective domains exhibited good convergent (item‐scale correlations > 0.40) and discriminant (items had higher correlation with their hypothesized scales than other scales) validity. Concurrent validity correlation coefficients of the FLSQ domain scores with the associated concurrent measures were acceptable (range: r = 0.40–0.70). Six FLSQ items demonstrated reliability and validity as stand‐alone items outside their domains. Conclusions: The FLSQ is a valid questionnaire for assessing treatment expectations, satisfaction, impact, and preference in adults with UFL.